What the World Needs Now: An Intervention for Promoting Prosocial Behavior. Issue 4 (4th July 2019) - Baumsteiger, Rachel
Abstract: Prosocial behavior benefits individuals and society. Thus, the purpose of this study was to develop a new, integrative intervention for fostering prosocial behavior. The intervention combines activities such as watching an elevating video, enacting prosocial behaviors, and reflecting on how those behaviors relate to one's values. An experiment with 116 adolescents and young adults indicated that the intervention was efficacious in enhancing prosocial behavior and related constructs (e.g., empathy) and that these effects were maintained 1 month later. These results have important implications for understanding and promoting prosocial habits.